ANALISIS SISTEM PENDIDIKAN ISLAM BERBASIS PESANTREN ANAK-ANAK TAHFIẒ AL-QUR’ÂN RAUDHATUL FALÂH BERMI GEMBONG PATI JAWA TENGAH - Falah, Ahmad (Program Studi Pendidikan Agama Islam, 2019)
Analysis Studi of Educational System in Institusional Traditional System (Pesantren) for children of Memorization Al-Qur’ân at Raudlatul Falâh Bermi Gembong Pati Central Java. This paper of research institutional system (pesantren) for children age 6/7 – 12 Th in Raudlatul Falah Bermi Gembong Pati Central Java. The fist program in institutional traditional system is memorization of al-Qur’ân 30 juz and learning is basic school (madrasa) /MI Tahfiẓ Raudlatul Falâh Gembong Pati Central Java. Educational system in institutional traditional include of teacher qur’an and teacher in basic shool, student, material or curriculum, methods of memorization of qur’ân, insfrastructure and environment education is dominant factor in succesfull system education aspecially in institutional traditional (pesantren)